Book Review: The SE Asian Gateway: History and Tectonic of the Australia-Asia Collision - Reijers, Tom J.A (Ikatan Ahli Geologi Indonesia, 2012)
The SE Asian Gateway: History and Tectonic of the Australia-Asia CollisionEdited by R. Hall, M. A. Cottam and M. E. J. WilsonGeological Society, London, Special Publication, 355, 2011, 381 pp. ISBN 978-1-86239-329-5.